ВЛИЯНИЕ ЭНДОМИКОРИЗЫ НА НЕКОТОРЫЕ БИОХИМИЧЕСКИЕ ПОКАЗАТЕЛИ РАСТЕНИЙ Avena sativa L. И Phaseolus vulgaris L. ПРИ ПОЧВЕННОМ ЗАГРЯЗНЕНИИ ТЯЖЕЛЫМИ МЕТАЛЛАМИ В УСЛОВЯХ ЛАБОРАТОРНОГО ЭКСПЕРИМЕНТА (Experimental biology, 2017)
It was comparing a mycorrhizal and nonmycorrhizal plant, growing on heavy metal (Pb, Cu, Zn) polluted soil. Arbuscular mycorrhiza increased plants tolerance to heavy metal.
Keywords: heavy metal; mycorrhiza